Do we have a national strategy against gender violence.? Ideas for its contruction with regard to D. Legislative N° 1368 - Hernández Alarcón, Christian (2018)
This text questions the way in whitch the state is fighting against violence affecting  women and members of the family group. The absence of a clear strategy as illustrated by recent advances and setbacks of regulatory amendments, show an intention of improvement that fails to consolidate despite the time elapsed since the entry into force of the law.In this context, the enactment of Legislative Decree 1368, which creates the Specialized Justice System to address some violence situations, represents a challenge that may serve to achieve the necessary interagency articulation and affectively wage this fight but this is still early considering that we do not even have the basic protocol for joint action, articulation instrument provided by Law 30364.